Nurul Hakim's Management In Improving The Education Quality For The Youth Of Kediri - Musta'in (LP2M IAI NURUL HAKIM, 2022)
This study aims to determine the efforts of the Pondok Pesantren Nurul Hakim in improving the quality of education for the youth of Kediri. This research was conducted at the Nurul Hakim Islamic Boarding School, Kediri, West Lombok, West Nusa Tenggara. This research used a case study with a qualitative descriptive approach. This study found two types of construction on society, which the construction of youth in the field of religious knowledge and construction of youth in the field of general science. That it could be concluded that the results of this study are the two types of coaching carried out by the management of the Nurul Hakim Islamic boarding school could improve the quality of education for the youth of Kediri.